Processo de produção escrita de professores que ensinam matemática em grupos de pesquisa - Barros, Márcia Alonso Tenório de (2016)
This qualitative research has the follow question: Which contribution provided by the teacher’s and future teacher’s written production that instruct math could be identified in a practice community? The research subjects create an heterogeneous group, consisted in general teachers of starter years and specialists in the final years that teach math in elementary school, graduated in pedagogy, math and researchers of the math education from PUC/SP. We used as reference the theories of Wenger (1993) to understand the practices and dynamics of the group, considering an space of graduation for teachers that teach Math, who research and reflect about its practices. The data were collected during the group trajectory, specifically at the time where the teachers prepared themselves for the written production to forward to scientific event, as well as at meetings where reflections were taken after those events. We recorded the audio of those dates and toke notes where there was a moment of analysis. We used training narratives elaborated by teachers and recent graduate students, as well as the description of the group trajectory. Concluding the investigation, we realized that there was time of contribution of the group, and those contribution gave the necessary support for the members to write its practice reports, both issues related to the text structure and the relationship between the practice described and the corresponding theory, which enabled the security to present those reports in external events. This process of presentation in external events as an incentive of the group provided the necessary professional engagement. The result of the research also pointed out the importance of the collective reflection about practice, which enabled the members of the group to broaden perspectives about the math questions, both related to its profession and to its practices. By the performed analysis we can say that there were professional growth of those involved, validating the written production as means of teacher’s formation, specially teachers who instruct math